PRUE’S IMAGINATION ABOUT IMPASSABLE WILDERNESS ON COLIN MELOY’S NOVEL WILDWOOD - Syairiyah, Marthalita Nasichatus (Dinamika : Jurnal Sastra dan Budaya, 2019)
Syairiyah, Marthalita N, and Fanani, Abu Prue’s Imagination for Impassable Wilderness on Colin Meloy’s Novel of Wildwood.Keyword: Imagination, dream, and Impassable Wildernes This article studies the  imagination which appears in child’s mind on the novel of Wildwood written by Colin Meloy. Sometimes the children like to imagine with what they see, hear, and read. In this novel, Prue is one of the children who experiences adventure by her imagination.This study is conducted to enrich the topic about imagination. Imagination in the object is analyzed using dream theory by Sigmund Freud. This research is using qualitative method. The novel of Wildwood by Colin Meloy is the primary data source. While, the supporting data are taken from secondary data source.The researchers find a result of this study; Prue’s imagination before she entered the Impassable Wilderness. Her imagination sometimes seems real even though not all of their imagination become real. But, this novel makes one of the children becomes real when she faces the problem of that myth.